IMPLEMENTASI ALGORITMA BUBBLE SORT TERHADAP REKOMENDASI BERITA BERDASAKAN HISTORY BACAAN - Ramadhan, Hari; Rahmawati, Silvia (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Focusing on the many conveniences offered by online media, a new problem arises among readers who find it difficult to read because they have to search for certain news that they just want to read but are not displayed on the first page. Therefore, having a recommendation system on a news site is very necessary to make it easier for online media to display certain news that only readers want to read. Where news is new information or information about something that is happening, presented in print, broadcast, internet, or by word of mouth to third people or many people. With this recommendation system, readers no longer find it difficult to search for news that is often opened, because this system will display recommendations for news categories that are often opened at the beginning of the page for the reader. The advantage of this recommendation system is that all readers don't have to bother selecting and searching for certain news that visitors often read, because when the reader returns to the news site, the reader will immediately be treated to similar news that visitors often read. The recommendation system design here uses the PHP programming language with a website-based MySQL database using the Bubble Sort algorithm method and the Bubble Sort algorithm was chosen because the process of sorting data is by comparing the current element with the next element.